Seasonal and circadian patterns of herring gull ( Larus smithsoniansus ) movements reveal temporal shifts in industry and coastal island interaction - Gutowsky, S. E.; Baak, J. E.; Craik, S. R.; Mallory, M. L.; Knutson, N.; d'Entremont, A. A.; Allard, K. A. (Ecological solutions and evidence, 2023)
Anthropogenic food subsidies attract opportunistic generalists like gulls in high densities, which may lead to negative impacts on human communities and local ecosystems. Managing impacts requires understanding why gulls use particular natural or industrial sites at different times of day or phases of the breeding cycle. Use of natural and human‐influenced habitats likely varies temporally as gulls alter schedules and site selection to match the predictability of different resources as they vary through space and time relative to patterns in human activities (seasonal industries, the work week, working hours) and natural rhythms (daylight, tide cycles), while gull resource requirements and restrictions to movement also shift with changing reproductive demands. We quantified seasonal and circadian patterns in American herring gull ( Larus smithsoniansus ) interactions with anthropogenic and natural sites throughout breeding using GPS data from 15 gulls tracked over 3 years from two colonies. We examined the weekly probability of gull occurrence at distinct destinations (e.g. breeding colony, islands, offshore, fish processing plants), and how occurrence varied with time of day, weekday/weekend, tide phase and colony, using GLMMs with a binomial response for destination‐specific occurrence. Probability at the colony varied predictably through the breeding season (highest attendance from dusk to dawn, during incubation and early chick rearing), providing confidence in the modelling approach for detecting temporal patterns in behaviour. Gulls visited other islands mostly outside incubation and early chick rearing, and from dusk through the night, likely roosting. Occurrence offshore where interaction with fishing vessels is possible was highest from dusk to dawn, and differed among colonies, but was the most likely destination during incubation and early chick rearing. Occurrence at fish plants gradually increased until after fledging when attendance was highest from Aug‐Oct coincident with the peak of Atlantic herring ( Clupea harengus ) processing and was more likely during the weekdays, during working hours, and during low and flood tide. Gulls in southwest Nova Scotia, Canada, have the behavioural flexibility to adapt to both natural rhythms and human schedules when beneficial, enabling them to thrive in a region where industry and natural resources are abundant. These findings can provide information to guide when and where to test different subsidy management strategies locally, while also considering potential increased pressures on island ecosystems. We emphasise that management outcomes of reductions of food subsidies for opportunistic species depend on multiple factors, including availability of alternative food sources and timing of use.